MIDWIFERY CARE WITH A FOCUS ON WARM GALANGAL WATER IMMERSION THERAPY INTERVENTIONS TO REDUCE LEG EDEMA IN PREGNANT WOMEN IN THE THIRD TRIMESTER - Nieken Luhputu Anggraini; Rizki Sahara; Nurya Kumalasari (The Shine Cahaya Dunia Kebidanan, 2025)
Background; From the moment of conception all the way until the delivery of the baby, a woman goes through a gestational period that spans 40 weeks and is divided into three distinct trimesters. Discomforts like leg edema might be brought on by the physiological and physical changes that occur during pregnancy. To alleviate this swelling without resorting to medication, try soaking your feet in warm galangal water. There were 19,407 pregnant women in 2023, according to data from the Grobogan Regency Health Office. Around 476 of these women were in Trimester III, and 59 of them had leg edema. From January to April of 2024, 4,248 expectant mothers were recorded in Grobogan Regency. Among them, 87 were in Trimester III, and 13 of those ladies suffered from leg edema. The aim of this study is to be able to provide midwifery care with a focus on warm galangal water immersion therapy interventions to reduce leg edema in pregnant women in the third trimester. Method; This study used a descriptive research strategy based on a case study design and research on Varney's seven stages of care: assessment, data interpretation, potential diagnosis, anticipation, intervention, performance, and evaluation. Result; Pregnant women's feet experienced a marked improvement in their edema levels, going from grade 2 to zero before the intervention. The intervention of warm galangal water immersion in lowering leg edema has been successful, as indicated by this decrease. Conclusion; The case study concludes that the mother's leg edema was successfully alleviated after 5 days of bathing in warm galangal water.